PENGARUH DEBT TO EQUITY RATIO (DER) DAN CURRENT RATIO (CR) TERHADAP RETURN ON EQUITY (ROE) - D. Muhamad Yamin; Lilis Murdiyanti (Universitas La Tansa Mashiro, 2018)
This study aims to determine whether there is an effect of debt to equity ratio, current ratio on return on equity in Property and Real Estate companies listed on the Indonesia Stock Exchange for the 2017 period.In this study the method used is a quantitative method with a description approach. Data analysis techniques used are classic assumption tests, multiple linear regression analysis techniques, correlation analysis, determination coefficients, hypothesis testing, and also using the help of SPSS V20 for windows. The populationin this study are Property and Real Estate companies listed on the Indonesia Efect Exchange for 2017. There are 48 company populations and the sample in the study was 31 companies, the sampling method was purposive sampling. The data was originally as much as 31 after the transformation of the data into 24, data collection techniques used by the company documentation and financial reporting techniques.The results of the research from the t test partially show that the variable debt to equity ratio has a significant effect on return on equity. While the current ratio has no significant effect on return on equity. F test results simultaneously Debt to Equity and Current Ratio have a significant effect on return on equity in property and real estate companies listed on the Indonesia Stock Exchange (BEI) for the 2017 period.